A systematic review of school‐based, mainstream, oral language interventions for key stage 1 children. Issue 4 (23rd January 2019) - Sedgwick, Adrienne; Stothard, Jan
Abstract : Up to 50% of children starting mainstream school have speech, language and communication needs (SLCN). Furthermore, evidence links SLCN to poor academic performance and social, emotional and mental health needs. This research aimed to systematically review the literature for school‐based oral language interventions, intended for KS1 children, in a mainstream setting, to provide an evidence base of filtered information assessed for methodological quality and relevance. Studies were assessed using a quantitative assessment framework and data were reported using PRISMA guidelines. Seventeen studies met the inclusion criteria, although just ten were classified as 'best evidence' and included in the final synthesis. Nine of the studies reported significant positive effects of the intervention, suggesting improvements to children's general language skills/specific vocabulary acquisition are possible if deliverers are trained and adhere to the programme. Recommendations for future research also emerged from the review.